The Cost-Quality Paradox: Tinjauan Literatur Sistematis atas Peran Quality Cost dalam Strategic Positioning Perusahaan) - Yolanda Ramadhona; Muhammad Al Ghazali; Naufal Adiwidya Ramawi; Thomas Alvando Winarto; Rela Sari (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
In an increasingly dynamic business environment, companies are frequently confronted with a dilemma between reducing operational costs and improving product or service quality, a tension widely recognized as the cost-quality paradox. This study aims to examine the role of Total Quality Management (TQM) and Cost of Quality (CoQ) management as critical instruments in strengthening companies strategic positioning, while deconstructing the assumptions underlying Trade-Off Theory. Employing a Systematic Literature Review (SLR) through qualitative thematic analysis of 15 selected studies published between 2020 and 2026, this research synthesizes empirical and conceptual evidence on how strategic investment in prevention costs and continuous improvement mechanisms can minimize failure costs and eliminate hidden quality costs. The findings reveal that the cost-quality paradox is not a universal economic law, but a capability-conditional phenomenon that dissolves when organizations possess mature CoQ measurement systems, long-term managerial orientation, and cross-functional integration capabilities. The integration of CoQ with TQM principles, supported by Industry 4.0 technologies, enables companies to simultaneously achieve cost efficiency and quality differentiation through defect elimination and learning effect mechanisms. Strategic CoQ optimization serves as the foundation for companies to attain market differentiation, sustain customer satisfaction, and secure long-term competitive advantage.